Integrating disaster risk reduction education into coastal schools in Aceh, Indonesia - Nurmalahayati Nurdin; Teuku Badlisyah (Jurnal Geuthèë: Penelitian Multidisiplin, 2026)
The integration of Disaster Risk Reduction (DRR) education in coastal schools in Aceh is a strategic initiative at enhancing community resilience to natural hazards, particularly tsunamis and coastal flooding. Aceh faces significant challenges in safeguarding its vulnerable populations, especially children and students in coastal areas. This project is to incorporate DRR education into the school curriculum to increase awareness, preparedness, and response capabilities among students and educators. To achieve this, a qualitative and quantitative approach was employed, involving survey and collaboration with local education authorities, disaster management agencies, and community stakeholders. The methods included developing tailored educational materials, conducting teacher training workshops, and implementing interactive classroom activities such as simulations and drills. Students who participated in the program demonstrated a marked increase in their knowledge of disaster risks and appropriate response actions. Teachers reported improved confidence in delivering DRR content, and the integration of DRR education was successfully embedded into the school curriculum. This initiative contributed to building a culture of safety and resilience within coastal communities in Aceh, emphasizing the importance of education as a vital component of disaster risk management. DRR integration can be taught through contextual and participatory in terms of existing subject, extracurricular, and local wisdom.